Participação de macrófagos e citocinas (TNF- , IL-1 e IL-8) na modulação da nocicepção induzida no modelo de contorções abdominais - Thomazzi, Sara Maria (1996)
In lhe present study it was evaluated in vivo and in vitro lhe role of macrophages and cytokines in the trigger of nociceptive activity induced by inflammatory stimuli (zymosan, acetic acid, carrageenin and LPS) in a rnice model of abdominal writhes. The results showed that LPS- stimulated macrophages monolayers were able to induce the release of a macrophage factor (MNF) which was active in inducing nociceptive activity when injected intraperitoneally. The release of MNF was inhibited by the pretreatment of the macrophages with inhibitors of protein synthesis (cyclohexemide) and cytokines production (dexamethasone) but not by cyclo-oxygenase inhibitors (indomethacin or paracetamol), showing its probable protein origin. On the other hand, MNF induced- nociception was blocked in a dose-dependent manner by pretreatments of the animais with indomethacin, paracetamol or dexamethasone, partially reduced by pretreatment with guanethidine and atenolol, and totally abolished by association of guanethidine or atenolol with indomethacin.